Perbandingan Kurikulum Sejarah Indonesia dengan Negara Negara Asia Tenggara - Syarif, Nurul Hidayanti; Bahri, Bahri (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2025)
Diversity in the delivery and focus of historical material between Indonesia and its neighboring countries, which can influence the younger generation's understanding of regional identity and relations. This study aims to compare Indonesia's history curriculum with that of Southeast Asian countries in order to identify similarities, differences, and implications of the approaches adopted by each country in history education. The method used in this study is a literature review, where data is collected from various academic sources, including textbooks, education policy documents, and previous research papers. Data analysis was carried out qualitatively using content analysis techniques. The results of the study show that although there are similarities in major themes such as colonialism and the struggle for independence, there are significant differences in the way the material is presented and emphasized, which is influenced by the social, political, and cultural context of each country. Some countries emphasize the role of the local in historical development, while others emphasize the international perspective. The implication of these findings is the need for dialogue and collaboration between countries to integrate more inclusive historical perspectives into the curriculum, in order to enhance cross-cultural understanding and regional cooperation